KETAHANAN PANGAN RUMAH TANGGA PETANI KELAPA SAWIT SWADAYA DI KABUPATEN TULANG BAWANG - Alifia Marsa Aisy; Dwi Haryono; Raden Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The aims of this research are to analyze the level of food security, the factors that affect the level of food security, and efforts to increase the level of food security of palm oil farmer households (POFH). The research was conducted using a survey method in Tulang Bawang Regency by involving 67 respondents from POFH who were chosen by a simple random sampling. The results of the research showed that 47.76 percent of POFH were categorized as the most secure of food, 29.85 percent as less secure, 20.90 percent as vulnerable, and 1.49 percent as food insecure. The factors that positively affect household food security were household income, formal education level of household head, and ethnicity.  The factor that negatively affect household food security was the the number family members. The efforts to increase the level of food security by Government were monitoring the stock of rice, drafting food balance, Programs called Pengembangan Usaha Pangan Masyarakat (PUPM), Kawasan Rumah Pangan Lestari (KRPL) and Modal Pengembangan Pangan Pokok Lebel (MP3L). The efforts of palm oil farmer households were owing groceries (47.50%), do outside work of palm oil farmer (50.62%), and changing dietary habit (1.88%). Key words: cross-classification, food security, palm oil households.